Calcium status assessment at the population level: Candidate approaches and challenges. Issue 1 (31st August 2022) - Rana, Ziaul H.; Bourassa, Megan W.; Gomes, Filomena; Khadilkar, Anuradha; Mandlik, Rubina; Owino, Victor; Pettifor, John M.; Roth, Daniel E.; Shlisky, Julie; Thankachan, Prashanth; Weaver, Connie M.
Abstract: Inadequate dietary calcium intake is a global public health problem that disproportionately affects low‐ and middle‐income countries. However, the calcium status of a population is challenging to measure, and there are no standard methods to identify high‐risk communities even in settings with an elevated prevalence of a disease caused or exacerbated by low calcium intake (e.g., rickets). The calcium status of a population depends on numerous factors, including intake of calcium‐rich foods; the bioavailability of the types of calcium consumed in foods and supplements; and population characteristics, including age, sex, vitamin D status, and genetic attributes that influence calcium retention and absorption. The aim of this narrative review was to assess candidate indicators of population‐level calcium status based on a range of biomarkers and measurement methods, including dietary assessment, calcium balance studies, hormonal factors related to calcium, and health outcomes associated with low calcium status. Several promising approaches were identified, but there was insufficient evidence of the suitability of any single indicator to assess population calcium status. Further research is required to develop and validate specific indicators of calcium status that could be derived from the analysis of data or samples that are feasibly collected in population‐based surveys. Abstract : Inadequate dietary calcium intake is a global public health problem that disproportionately affects low‐ and middle‐income countries (LMICs). However, the calcium status of a population is challenging to measure. This narrative review assesses candidate indicators of population‐level calcium status based on a range of biomarkers and measurement methods such as dietary assessment, calcium balance studies, and hormonal factors related to calcium.